Relationship Between Working Posture and Musculoskeletal Complaints IN Rice Factory Workes In Lapao-Poa Village, Wolo District, Kolaka Regency, Southeast Sulawesi - Ummi, Virsa Aulia; Amir, Suliati P.; Mulyadi, Farah Ekawati; Sam, Andi Dhedie Prasatia; Putra, Fadil Mula (Syifa'Medika, 2026)
This study aims to analyze the relationship between non-ergonomic work postures and musculoskeletal complaints among rice factory workers in Lapao-Pao Village, Wolo Subdistrict, Kolaka District, Southeast Sulawesi. The study employed a cross-sectional design with an observational analytical approach, involving 30 workers divided into three work groups: PPAB, PPTAB, and PBTAB. Work postures were assessed using the Rapid Entire Body Assessment (REBA) method, while musculoskeletal complaints were measured using the Nordic Body Map. The results of the study showed that the majority of respondents experienced mild musculoskeletal complaints; however, no significant relationship was found between work postures and musculoskeletal complaints, with p-values greater than 0.05. Nevertheless, the analysis indicated that groups with high work posture risk were more likely to report more musculoskeletal complaints. This study emphasizes the importance of ergonomic interventions, such as proper work posture training and better workplace design, to reduce musculoskeletal complaints. Additionally, this study provides recommendations for further research using a longitudinal approach to identify other factors influencing the relationship between work posture and musculoskeletal complaints